ANALISIS KESIAPAN DAN MINAT MAHASISWA DALAM PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA: STUDI KASUS MAHASISWA JPTK FKIP UNS ANGKATAN 2020 - Mukhlis Dwiaji Pamungkas; Budi Harjanto; Towip Towip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
It is necessary to increase soft skills and hard skills so that university graduates are ready to work and face challenges in the world of work. Competencies are needed that are integrated with other majors so that university graduates can adapt to the world of work. So that students must be prepared to have readiness and interest in learning in the era of global competition. The Independent Learning Campus Merdeka Program (Program Merdeka Belajar Kampus Merdeka atua MBKM) is expected to be able to answer this challenge. The method used in this research is descriptive statistics. With the aim of testing the hypothesis that there is readiness, interest, and major indicators that affect the readiness and interest of JPTK FKIP UNS students batch 2020 in carrying out the Independent Learning Campus Merdeka program. The conclusion of this study is that there is readiness of JPTK FKIP UNS students batch 2020 in the MBKM program, there is interest from JPTK FKIP UNS students batch 2020 in the MBKM program, there are large indicator values that affect the readiness and interest of JPTK FKIP UNS students batch 2020 in implementing the MBKM program, namely indicators Emotions of Pleasure and Psychic Conditions Affective Attitudes.